The study of the relevance of macro- and microelements in the hair of young wrestlers depending on the style of wrestling - Zaborova, Victoria; Zolnikov, Oxana; Dzhakhaya, Natiya; Bueverova, Elena; Sedova, Alla; Kurbatova, Anastasia; Putilo, Victor; Yakovleva, Maria; Shantyr, Igor; Kastyro, Igor; Ozimek, Mariusz; Korolev, Dmitry; et al. (Frontiers in Endocrinology, 2022)
While participating in an intensive training process, the athlete’s body requires not only energy, but also specific macro- and microelements. The purpose of this study was to show the meaning of monitoring the level of mineral trace elements in athletes-wrestlers during physical activity. As an experimental group, 66 male wrestlers aged 18-20 years with at least 3 years of professional wrestling experience were examined. The control group consisted of 92 young cadets of military school aged 18-20 years, who had previous sports training, but were not engaged in wrestling. To determine the quantitative content of trace elements, the hair was cut from the back of the head for the entire length in an amount of at least 0.1 g. an examined using the mass spectrometer ICP-MS Agilent 7900. Strong positive correlations were found for sodium with potassium and rubidium, magnesium with calcium, potassium with rubidium, and rubidium with caesium among wrestlers. Wrestlers were found to have higher levels of a number of macro- and microelements, including toxic ones.